Impact of Wheat Harvest on Levels and Sources of PM2.5-associated PAHs in an Urban Area Located at the Center of Beijing-Tianjin-Hebei Region - Zhiyong Li; Zhenxin Li; Ziyuan Yue; Dingyuan Yang; Yutong Wang; Lan Chen; Songtao Guo; Jinsong Yao; Lei Wang; Xiao Lou; Xiaolin Xu; Jinye Wei; et al. (Aerosol and Air Quality Research, 2021)
Abstract Wheat harvest and subsequent straw burning for maize planting can cause severe PM2.5 and PAH pollutions and deteriorate the air quality of nearby cities in consequence. PM2.5 samples were collected in Baoding urban area (BUA) from June 18 to July 7 of 2019, during and after wheat harvest (DWH and AWH, respectively). The “Migration Effect” (i.e., PM2.5 and PAHs transferred from rural to urban during DWH and AWH, respectively) was proved by both the later time for appearance of peak values of PM2.5 and PAHs and the air mass origins in BUA. The daily average PM2.5 (reported in µg m–3) 137 of DWH was 2.58 times 53.1 of AWH for BUA, regardless of its lower levels than the corresponding 156 and 75.6 for an adjacent rural site (ARS). The reverse trend was found for PAH mass contents (in µg g–1), AWH possessed much higher value of 139 than 27.8 of DWH, while no significant fluctuations occurred for PAH concentrations due to the varied PM2.5 levels. Four PAH sources including biomass burning (BB), coal combustion (CC), vehicle exhaust (VE) and industrial emissions (IN) were identified using positive matrix factorization (PMF). BB was the biggest contributor during whole sampling period (WSP), followed by CC, VE, and IN. BB increased from 17.3% to 37.1% along with the transition from DWH to AWH, indicated the impact of straw burning for maize planting. High share of CC suggested that coal was still an important civil fuel. The strict emission reduction measures made the industry smallest contributor in BUA. Lower VE share in BUA than ARS demonstrated that influence of high-intensity operation of wheat harvesters and rotary cultivators.